Effect of TIVA with Propofol Versus Inhalational Anasthesia Plus Ketamine on Fertilization and Clinical Pregnancy Rate in ICSI - Ghazi Reshan, Raad; Ghanim Ameen , Bashar; Abdulrazzaq Hassan, Asmaa (International Journal of Psychosocial Rehabilitation, 2020)
Anesthesia is an important part of in vitro fertilization and can be detrimental to the reproductive result due to potential toxicity encountered by the anesthetic drugs used. Place and duration of the study: The study is held at the High Institute of Infertility and ARTs at al-Nahrin University in Baghdad, Iraq, from the 1st of April 2018 to the 1st of February 2019. Material and methods: 80 patients during their ICSI course were randomized blindly at the time of oocyte retrieval anesthesia into two groups: 40 patients subjected to TIVA (total intravenous anesthesia) with midazolam and propofol (group 1) and 40 patients subjected to inhalational anesthesia (isoflurane ) with ketamine and midazolam. Evaluation of fertilization, cleavage, grade 1 embryo, and pregnancy rate was done to determine the more beneficial and less toxic anesthesia for in vitro fertilization patients. Conclusion: TIVA with midazolam and propofol had better reproductive outcomes on fertilization rate, cleavage, and grade 1 embryo rate with a significantly higher pregnancy rate than inhalational anesthesia with midazolam and ketamine.